(untitled) (Bangladesh Journal of Medicine, 2024)
Functional neuroimaging is a major tool in the study of neurological illnesses. It plays a role in diagnosis, therapy, and surgical planning. It can aid in the identification and understanding of functional movement impairments, as well as their differentiation from other diseases. It can also aid in detecting co-morbid organic illnesses. Positron-emission tomography (PET) and single-photon-emission computed tomography (SPECT) are well-known nuclear-medicine imaging techniques utilized in current neurological diagnostics. PET (Positron Emission Tomography) and SPECT (Single Photon Emission Computed Tomography) are two imaging procedures that use radioactive tracers to analyze the brain and other organs. They are essential in both clinical research and treatment development, and can aid in the early detection and treatment of neurological diseases. So, the combination of PET with 18F-fluorodeoxyglucose (FDG) and SPECT with a 111 In-labeled ligand provides clinicians with information an other kind of neurological disorders. Bangladesh J Medicine 2025; 36: 3-14